Factors Associated with Stalking Duration Among a Nationally Representative Sample: Results from the 2010 National Intimate Partner and Sexual Violence Survey - Hayes, Brittany E. (Violence against women, 2023)
The current study examined the duration of stalking episodes among a nationally representative sample. Analyses of the National Intimate Partner and Sexual Violence Survey estimated if the victim–perpetrator relationship and other types of victimization experienced were associated with (a) if the stalking episode lasted over a year (N = 1,509) and (b) the length of stalking episodes, in days, for episodes <1 year (N = 506). Findings indicate coercive control was associated with higher odds the stalking episode lasted over a year and increased the length of episodes lasting <1 year. The intersection of stalking and coercive control is discussed.